2011
DOI: 10.1097/ncc.0b013e3181fb3686
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Following Hematopoietic Stem Cell Transplantation

Abstract: Background-Patients receiving high-dose chemotherapy and hematopoietic stem cell transplantation (HSCT) experience considerable reductions in physical activity and deterioration of their health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
139
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 38 publications
2
139
0
3
Order By: Relevance
“…7 Since this review, six new randomized controlled trials have been published, supporting these findings; some studies showed strong effects for body composition as well as weaker but promising effects for cardiorespiratory fitness, fatigue, muscle strength, physical functioning and quality of life. [8][9][10][11][12][13] Nevertheless, many questions remain unanswered regarding exercise interventions in HCT patients. Additional evidence is required to determine the optimal exercise recommendation, with respect to amount, type, intensity and time point for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…7 Since this review, six new randomized controlled trials have been published, supporting these findings; some studies showed strong effects for body composition as well as weaker but promising effects for cardiorespiratory fitness, fatigue, muscle strength, physical functioning and quality of life. [8][9][10][11][12][13] Nevertheless, many questions remain unanswered regarding exercise interventions in HCT patients. Additional evidence is required to determine the optimal exercise recommendation, with respect to amount, type, intensity and time point for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies used the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire [11,12,16,17,21], while one study used the Cancer Rehabilitation Evaluation System [19], and another used the Medical Outcomes Study 36-Item Short Form [23]. Some studies revealed significantly higher QOL scores for the allogeneic intervention group than those for the allogeneic control group [11,12,17,19].…”
Section: Quality Of Lifementioning
confidence: 99%
“…The onset timing of physical exercise intervention for allo-HSCT patients varies, and can occur in 1 of 3 phases: conditioning (before HSCT) [11][12][13][14][15][16][17], post engraftment (after HSCT) [18,19], or hospital discharge phase [20][21][22][23][24]. Recently, physical exercise intervention has reportedly been increasingly initiated during the conditioning phase (chemotherapy and radiation therapy regimen).…”
Section: Physical Exercise Intervention Periodmentioning
confidence: 99%
See 2 more Smart Citations